Robotic-assisted thoracoscopy thymectomy for juvenile myasthenia gravis - F. Grasso; L. De Leonibus; M. Bertozzi; M. Sica; R. Angotti; L. Luzzi; F. Molinaro; M. Messina; P. Paladini (Elsevier, 2020)
Introduction: Juvenile myasthenia gravis (JMG) is a rare debilitating and potentially fatal autoimmune disease, with unclearify pathogenesis. Surgical immunomodulation with thymectomy has been repeatedly demonstrated to be a safe and effective treatment for JMG in both adult and pediatric patients. In the last few years, minimally invasive approach and above all robotic assisted thoracoscopy, replaced sternotomy which is widely used in adult patients. We report our experience in a case of robot-assisted thoracoscopic thymectomy approach in a 12 years old boy for juvenile myasthenia gravis (JMG). Case report: Procedure was performed with the Da Vinci surgical robot (Xi) using left-sided approach. Left lung was kept out from mechanic ventilation. A 8 mm port for the 3-D camera was introduced on the V intercostal space on the anterior axillary line. Others two 8mm thoracic ports were placed under vision after the induction of a low-pressure pneumothorax, respectively on the midaxillary line on the III intercostal space and on the parasternal space on the V intercostal space. Bulk resection of gland was made using Maryland grasper and Harmonic scalpel, starting at level of the left pericardiophrenic angle and continuing cranially. Thymus was unstick from the posterior face of the sternum until the right pleura releasing lower thymic horns. After that, controlateral right-side thymectomy was continued into the neck to include the upper horns and finally it was removed with an endocatch bag. Histopathological examination showed a benign thymic hyperplasia. There were no perioperative and postoperative complications. The discharge was on IV post-operative day. After thymectomy, patient reported an improvement in symptoms and stopped medical therapy with pyridostigmine. Conclusions: VATS and Robotic thoracoscopic thymectomy have increasingly taken hold in recent years. The surgical treatment offered to patient an improvement in clinical status. Surgery by robotic assistance has demonstrable advantages, including three-dimensional visualization and articulating instruments. Left lateral approach provided excellent visualization of the thymic veins, anonymous vases and phrenic nerves. Three-dimensional visualization as well as articulating arms greatly facilitated the dissection compared with standard thoracoscopic technique. In Literature very few series of robotic approach for surgical treatment of JMG in children are reported, for these reasons further studies are needed.